“Message to youth”. Luis Jiménez de Asúa and the student movement opposed to the Primo de Rivera Dictatorship - Martínez Cánovas, Gonzalo J. (CIAN-Revista de Historia de las Universidades, 2021)
During the Primo de Rivera Dictatorship, the student movement underwent a series of changes so profound that they brought it from its traditional atony attitude to the forefront of Spanish public life. His manifestations of dissidence against the regime were based not only on the interventionist policy of the Dictatorship, but also on subversive attitudes towards widely established social conventions and customs. On the other hand, not few of those youthful protagonists, as well as some of the most notable historiographical works, have considered Luis Jiménez de Asúa to be the most outstanding of the protester professors. He is a professor of criminal law at the Central University and is considered a spiritual guide among liberal youths. During that decade, Asúa also experienced a deep process of personal transformation. The following article approaches this convergent process, taking as a symbolic-chronological frame of reference two representative manifestos of the Madrid jurist, tributary as well as two radically different contexts: Impressions of Argentina (15/10/1923) and Message to the Youth. Re-turn to Science (17/04/1931).
Keywords: Spain; student movement; Luis Jiménez de Asúa; Primo de Rivera’s dictatorship; university